Rhodium-Catalyzed Intramolecular Acylation of 2-(Indol-1-yl)-benzoic Acids under Redox-Neutral Conditions - Suzuki, Hirotsugu; Takemura, Yosuke; Matsuda, Takanori (Synlett, 2023)
We developed a novel access to indoloindolone by a rhodium-catalyzed intramolecular acylation of 2-(indol-1-yl)benzoic acids. This reaction proceeds via the in situ formation of a mixed anhydride under redox-neutral reaction conditions. Preliminary mechanistic investigations revealed that the in situ formed mixed anhydride participates in the C–H activation step, which is facilitated by a RhI catalyst. The utility of this reaction was demonstrated by a large-scale reaction.
Keywords: rhodium; intramolecular acylation; redox-neutral conditions; indoloindolones; C–H activation